Political Issues in Social Media Campaigns for National Elections: A Plea for Comparative Research - Bene, Márton (2024)
As ideological, class-based voting has waned, issue-based voting has become more prevalent. Political parties can sway election outcomes by promoting certain topics, particularly on social media, which has become pivotal to political communication. However, our understanding of political actors’ social media strategies remains limited. This thematic issue, based on the international research project Digital Election Campaigning Worldwide (DigiWorld), aims to broaden such understanding. Examining 14 countries across Western Europe, Eastern Europe, North America, Latin America, and Oceania, the 10 articles in this issue reveal diverse approaches to issue-based political communication on social media, emphasizing the significance of comparative research in this field.